La enfermedad en las cartas de Gertrudis Gómez de Avellaneda: claves para un diagnóstico - Ángeles Ezama Gil (Cuadernos de Ilustración y Romanticismo)
Sickness is a recurring leit-motiv in personal writings of 19th century women writers. Among the Spanish Women there are only a few writings known and a very reduced bibliography about it. Thus, this research seeks to open up a new perspective both in the analysis of the epistolary genre and in the way in which the issue of female disability is interpreted in letters. The epistles of Gertrudis Gómez de Avellaneda reveal that she suffered throughout her life from different physical and psychological illnesses. She experienced variated symptoms of barely described and hardly identifiable diseases, which could be explained by her conditions of poet and woman. The first explains an attitude to the world tinged with tedium (ennui or spleen). The second leads us to the topic of sick woman characteristic of the 19th century society.